Composite positive electrode material and preparation method thereof, positive electrode plate, battery and electric equipment

By mixing materials such as lithium iron phosphate with LiNiyBzC1-y-zO2, composite positive electrode materials are prepared, which solves the safety problem of negative electrode-free lithium batteries when thermal runaway, and achieves high safety and good electrochemical performance of the batteries.

CN119812238APending Publication Date: 2025-04-11BYD CO LTD

Patent Information

Application Number
CN202411552118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing negative electrode-free lithium batteries are prone to risk of fire when thermally out of control, and have insufficient safety.

Method used

A composite positive electrode material is used, which is mixed with LiNiyBzC1-y-zO2 as the first component and LiNiyBzC1-y-zO2 as the second component, and is prepared by physical mixing method to ensure that the mass ratio of the first component and the second component is within the range of (9-5): (1-5).

Benefits of technology

It improves the safety performance of the battery, prevents the chain reaction when thermal runaway, enhances the thermal stability of the battery, while maintaining high electrochemical performance and capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115954260000111
    Figure BDA0005115954260000111
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and provides a composite positive electrode material, a preparation method of the composite positive electrode material, a positive electrode plate, a battery and electric equipment. The composite positive electrode material comprises a first component and a second component, the first component comprises at least one of LiFePO4 (lithium iron phosphate), LiCoPO4 (lithium cobalt phosphate), LiMnPO4 (lithium manganese phosphate), LiNiPO4 (lithium nickel phosphate) and LiMnxFe (1-x) PO4; wherein 0.2 < = x < = 0.8; the second component comprises LiNi < y > B < z > C < 1-y-z > O < 2 >; wherein B comprises at least one of Co, Al and Mn, and C comprises at least one of Co, Al and Mn, 0 lt; yt; Yt; 1, 0lt; zlt, zlt; 1; the mass ratio of the first component to the second component is (9-5): (1-5). When the mixed positive electrode is applied to a battery system, the safety of the battery is improved while the high capacity is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and particularly relates to a composite cathode material and a preparation method thereof, as well as a cathode electrode sheet, a battery and an electrical device. Background Art

[0002] The lithium metal-free battery is a new battery technology. It may not directly use traditional anode materials, but they still need to have a structure or region capable of receiving and releasing lithium ions. The lithium metal-free battery avoids the direct use of lithium metal, greatly simplifies the production process and reduces the production cost. Therefore, it has received wide attention as a new type of battery.

[0003] However, the existing technical solutions are limited to the research on aspects such as lithium deposition behavior, improving cycle life and capacity improvement, and there are few reports on how to improve the safety of lithium metal-free batteries. Summary of the Invention

[0004] The present invention aims to solve at least to some extent the safety problem of lithium metal-free batteries. To this end, an object of the present invention is to provide a composite cathode material and a preparation method thereof, as well as a cathode electrode sheet, a battery and an electrical device. The composite cathode material has good thermal stability, so that the lithium metal-free battery exhibits excellent safety performance.

[0005] In the first aspect of the present application, a composite cathode material is provided. According to an embodiment of the present application, the composite cathode material includes a first component and a second component; the first component includes at least one of LiFePO4 (lithium iron phosphate), LiCoPO4 (lithium cobalt phosphate), LiMnPO4 (lithium manganese phosphate), LiNiPO4 (lithium nickel phosphate) and LiMn x Fe 1-x PO4 (lithium manganese iron phosphate); wherein, 0.2 ≤ x ≤ 0.8; the second component includes LiNi y B z C 1-y-z O2; wherein, B includes at least one of Co, Al and Mn, C includes at least one of Co, Al and Mn, 0 < y < 1, 0 < z < 1; the mass ratio of the first component to the second component is (9 - 5):(1 - 5).

[0006] The composite positive electrode material provided in the embodiment of the present application is conducive to improving the safety of the battery. The embodiment of the present application mixes the first component with the second component as the main positive electrode active material. On the one hand, it is conducive to reducing the chance of direct contact between the electrolyte and the main positive electrode active material (i.e., the second component), thereby improving the stability of the structure of the main positive electrode active material; on the other hand, the first component is an olivine structure, which has a high thermal stability, and is conducive to preventing the chain reaction when the main positive electrode active material is in thermal runaway, thereby improving the safety of battery use. The composite positive electrode material provided in the embodiment of the present application exhibits good electrochemical properties. In the composite positive electrode material of the embodiment of the present application, the first component and the second component material have similar voltage platforms, so the composite positive electrode material obtained by compounding the two components can still maintain a relatively high capacity.

[0007] According to an embodiment of the present invention, the composite positive electrode material may further include at least one of the following additional technical features:

[0008] In some embodiments, the mass ratio of the first component to the second component is (7-5):(3-5).

[0009] In some embodiments, LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different.

[0010] In some embodiments, the first component is LiMn x Fe 1-x PO4.

[0011] In some embodiments, the particle size of the first component is smaller than the particle size of the second component.

[0012] A second aspect of the present application provides a positive electrode plate, comprising the above-mentioned composite positive electrode material.

[0013] The positive electrode plate provided in the present application comprises the above-mentioned composite positive electrode material and exhibits good electrochemical performance and safety performance.

[0014] In some embodiments, the positive electrode sheet includes a positive electrode current collector and an active material layer, and the active material layer includes the above-mentioned composite positive electrode material.

[0015] In some embodiments, the mass percentage of the composite positive electrode material in the active material layer is 90 wt % to 95 wt %.

[0016] A third aspect of the present application provides a battery, comprising the above-mentioned positive electrode plate.

[0017] The battery provided in this application exhibits good safety and high electrochemical performance.

[0018] In some embodiments, the battery further includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector.

[0019] In some embodiments, the negative electrode current collector includes at least one of a copper foil, a porous copper foil, and a brass foil.

[0020] In some embodiments, the battery is a negative electrode-less lithium battery.

[0021] A fourth aspect of the embodiments of the present application provides an electrical device comprising the above-mentioned battery.

[0022] The electrical device may be an electric car, an electric motorcycle, an electric bicycle, a mobile phone, a computer, a camera, an e-book player or a wearable device.

[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0024] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0025] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0028] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequent described event or condition may but does not necessarily occur, and this description includes the cases where the event or condition occurs and the cases where the event or condition does not occur.

[0029] The solution of the present invention will be explained below in conjunction with embodiments. Those skilled in the art will understand that the following embodiments are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. For those without specific technical or conditions noted in the embodiments, they shall be carried out according to the technologies or conditions described in the literature in the art or according to the product specifications. For the reagents or instruments without the manufacturer noted, they are all conventional products that can be obtained through commercial purchase.

[0030] The lithium metal-free lithium battery avoids the direct use of a lithium metal anode, greatly simplifies the production process and reduces the production cost, and thus has received extensive attention as a new type of battery. Since the lithium metal-free battery does not have the buffering of the traditional active material layer at the anode, when the battery thermal runaway occurs, the heat increases rapidly, and there is an easy risk of fire. The existing technical solutions are limited to the research on aspects such as lithium deposition behavior, improving cycle life and capacity improvement, and there are few reports on how to improve the safety of the lithium metal-free lithium battery. The above traditional active materials refer to graphite, hard carbon, silicon-based materials, etc. used in current batteries.

[0031] In the first aspect of the embodiments of the present application, a composite cathode material is provided, including a first component and a second component; the first component includes at least one of LiFePO4 (lithium iron phosphate), LiCoPO4 (lithium cobalt phosphate), LiMnPO4 (lithium manganese phosphate), LiNiPO4 (lithium nickel phosphate) and LiMn x Fe 1-x PO4 (lithium manganese iron phosphate); wherein, 0.2 ≤ x ≤ 0.8; the second component includes LiNi y B z C 1-y-z O2; wherein, B includes at least one of Co, Al and Mn, C includes at least one of Co, Al and Mn, 0 < y < 1, 0 < z < 1; the mass ratio of the first component to the second component is (9 - 5):(1 - 5).

[0032] The composite positive electrode material provided in the embodiment of the present application is conducive to improving the safety of the battery. The embodiment of the present application mixes the first component with the second component as the main positive electrode active material. On the one hand, it is conducive to reducing the chance of direct contact between the electrolyte and the main positive electrode active material (i.e., the second component), thereby improving the stability of the structure of the main positive electrode active material; on the other hand, it is conducive to hindering the chain reaction of the main positive electrode active material during thermal runaway, thereby improving the safety of battery use. In addition, the first component is an olivine structure with high thermal stability, which plays a good role in improving the overall safety of the composite positive electrode material. The above main positive electrode materials refer to the positive electrode active materials commonly used in linear battery systems.

[0033] The composite cathode material provided in the embodiment of the present application exhibits good electrochemical performance. In the composite cathode material of the embodiment of the present application, the first component and the second component have similar voltage platforms, so the composite cathode material obtained by compounding the two components can still maintain a relatively high capacity.

[0034] In the embodiment of the present application, the mass ratio of the first component to the second component is combined with the above design, which is conducive to the separation and barrier effect, promotes uniform dispersion, and effectively prevents the chain reaction when the battery thermal runaway occurs. Further, in the mass ratio of the first component to the second component, the sum of the first term and the second term is 10.

[0035] In the embodiment of the present application, the second component includes LiNi y B z C 1-y-z O2; wherein B and C may be the same or different.

[0036] If B and C are the same, the second component is a binary material, that is, a binary active positive electrode material.

[0037] If B and C are different, the second component is a ternary material, that is, a ternary active positive electrode material.

[0038] In specific examples, the mass ratio of the first component to the second component is 9:1, 8:2, 7:3, 6:4, 5:5, etc.

[0039] In some embodiments, the mass ratio of the first component to the second component is (7-5):(3-5). Further, the sum of the first term and the second term satisfying the mass ratio is 10.

[0040] The mass ratio of the first component and the second component in the embodiment of the present application is in the above-mentioned ratio range, which is conducive to further improving the separation and barrier effect, and effectively preventing the chain reaction from occurring during thermal runaway. Based on the thermal stability of the first component itself, adding more of the first component is conducive to effectively improving the overall safety of the composite positive electrode material without affecting the normal use of the battery.

[0041] In some embodiments, the second component is LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different.

[0042] Ternary materials are widely used as positive electrode active materials. The embodiments of the present application use ternary materials in combination with the first component and are applied to batteries. They show good electrochemical properties and high safety and have important market application value.

[0043] In some embodiments, the first component is LiMn x Fe 1-x PO4, where 0.2≤x≤0.8.

[0044] In the embodiment of the present application, lithium manganese iron phosphate is used as the first component, which is closer to the voltage platform of the second component ternary material and has an olivine structure, which is conducive to obtaining better safety and better electrochemical performance.

[0045] In some embodiments, the particle size of the first component is smaller than the particle size of the second component.

[0046] In the embodiment of the present application, by dispersing the first component with a smaller particle size between the second component with a larger particle size, the second component particles are well dispersed and isolated. On the one hand, it is beneficial to reduce the direct contact between the electrolyte and the second component, thereby improving the stability of the second component structure; on the other hand, it effectively prevents the chain reaction of the second component during thermal runaway, which is beneficial to improving safety.

[0047] In the embodiment of the present application, the average particle size of the first component may be larger than the average particle size of the second component. The average particle size may be D 50 express.

[0048] In a specific example, the average particle size of the first component is between 200nm and 400nm, and the average particle size of the second component is between 3μm and 5μm; or, the average particle size of the first component is 300nm, and the average particle size of the second component is 5μm; or, the average particle size of the first component is 100nm, and the average particle size of the second component is 1μm, etc.

[0049] The second aspect of the embodiment of the present application provides a method for preparing a composite positive electrode material, comprising: physically mixing a first component and a second component to obtain a composite positive electrode material; the first component comprises LiFePO4, LiCoPO4, LiMnPO4, LiNiPO4 and LiMn x Fe 1-x PO4; wherein 0.2≤x≤0.8; the second component includes LiNiy B z C 1-y-z O2; wherein, B comprises at least one of Co, Al, and Mn, C comprises at least one of Co, Al, and Mn, 0 < y < 1, 0 < z < 1; the mass ratio of the first component to the second component is (9 - 5):(1 - 5).

[0050] In the embodiments of the present application, the first component is physically mixed with the second component as the cathode active material. On the one hand, it is beneficial to reduce the chance of direct contact between the electrolyte and the cathode active material (i.e., the second component), and improve the structural stability of the cathode active material; on the other hand, it is beneficial to hinder the chain reaction that occurs when the cathode active material is in thermal runaway, thereby improving the safety of battery use. In addition, the first component has an olivine structure and has relatively high thermal stability, which plays a very good role in improving the overall safety of the composite cathode material.

[0051] The composite cathode material provided by the embodiments of the present application exhibits good electrochemical performance. In the composite cathode material of the embodiments of the present application, the first component and the second component materials have similar voltage platforms, so the composite cathode material obtained by the compounding of these two components can still maintain a high capacity.

[0052] The preparation method provided by the embodiments of the present application directly physically mixes the first component and the second component, with simple process, convenient operation, low production cost, and is conducive to large-scale production.

[0053] In some embodiments, the physical mixing method includes mechanical mixing, solution co-blending, powder mixing, etc. It can be a single physical mixing method or a combination of multiple physical mixing methods.

[0054] In the embodiments of the present application, the mass ratio of the first component to the second component is (9 - 5):(1 - 5). In specific examples, the mass ratio of the first component to the second component is 9:1, 8:2, 7:3, 6:4, 5:5, etc. In the embodiments of the present application, the mass ratio of the first component to the second component conforms to the above design, which is beneficial to fully exert the separation and barrier effects, promote uniform dispersion, and effectively hinder the chain reaction during thermal runaway. Further, the sum of the antecedent and the consequent of the mass ratio of the first component to the second component is 10.

[0055] In some embodiments, the mass ratio of the first component to the second component is (7 - 5):(3 - 5). Further, the sum of the antecedent and the consequent of the mass ratio is 10.

[0056] The mass ratio of the first component and the second component in the embodiment of the present application is in the above-mentioned ratio range, which is conducive to further improving the separation and barrier effect, and effectively preventing the chain reaction from occurring during thermal runaway. Based on the thermal stability of the first component itself, adding more of the first component is conducive to effectively improving the overall safety of the composite positive electrode material.

[0057] In some embodiments, LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different.

[0058] In some embodiments, LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different; and / or the first component is LiMn x Fe 1-x PO4.

[0059] Ternary materials are widely used as positive electrode active materials. The embodiments of the present application use ternary materials in combination with the first component and are applied to batteries. They show good electrochemical properties and high safety and have important market application value.

[0060] In a specific example, LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different; and the first component is LiMn x Fe 1-x PO4.

[0061] In the embodiment of the present application, lithium manganese iron phosphate is used as the first component, which is closer to the voltage platform of the second component ternary material and has an olivine structure, which is conducive to obtaining better safety and better electrochemical performance.

[0062] A third aspect of an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned composite positive electrode material, or comprising the composite positive electrode material obtained by the above-mentioned preparation method.

[0063] The positive electrode plate provided in the embodiment of the present application comprises the above-mentioned composite positive electrode material and exhibits good electrochemical performance and safety performance.

[0064] In some embodiments, the positive electrode sheet includes a positive electrode current collector and an active material layer, and the active material layer includes the above-mentioned composite positive electrode material, or includes the composite positive electrode material obtained by the above-mentioned preparation method.

[0065] In the embodiment of the present application, the active material layer including the composite positive electrode material and the positive electrode current collector can be combined to form a positive electrode sheet.

[0066] In some embodiments, the positive current collector includes a positive metal current collector.

[0067] Furthermore, the positive electrode metal current collector includes an aluminum foil with a conductive coating on the surface. Furthermore, the conductive coating is at least one of graphene, acetylene black and carbon nanotubes, and the thickness of the conductive coating is 2μm to 5μm. The primer coating is provided on the aluminum foil, in addition to increasing the conductivity of the positive electrode sheet and improving the battery rate performance, in this solution, the most important role of the conductive coating is to act as a buffer medium to buffer the heat diffusion during thermal runaway of the battery and increase the safety performance of the battery.

[0068] In some embodiments, the mass percentage of the composite positive electrode material in the active material layer is 90 wt % to 95 wt %.

[0069] In the embodiment of the present application, the mass percentage of the composite positive electrode material in the active material layer is 90wt% to 95wt%, which is conducive to obtaining a positive electrode sheet with good electrochemical performance. In a specific example, the mass percentage of the composite positive electrode material in the active material layer is 90wt%, 91wt%, 92wt%, 93wt%, 94wt% or 95wt%, etc.

[0070] In some embodiments, the active material layer further includes a binder and a conductive agent.

[0071] Furthermore, the mass percentage of the binder in the active material layer is 1 wt% to 5 wt%, and the mass percentage of the conductive agent in the active material layer is 2 wt% to 5 wt%.

[0072] Furthermore, the binder includes at least one of polytetrafluoroethylene and polyvinylidene fluoride.

[0073] Furthermore, the conductive agent includes at least one of graphene, acetylene black, carbon fiber and carbon nanotube.

[0074] A fourth aspect of an embodiment of the present application provides a battery, comprising the above-mentioned positive electrode plate.

[0075] The battery provided in the embodiments of the present application exhibits good safety and high electrochemical performance.

[0076] In some embodiments, the battery further includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector.

[0077] In some embodiments, the battery is a negative electrode-free lithium battery.

[0078] In some embodiments, the negative electrode current collector comprises at least one of copper foil, porous copper foil and brass foil. Further, the thickness of the negative electrode current collector is 8 μm to 12 μm.

[0079] In some embodiments, the battery is a negative electrode-free lithium battery.

[0080] The battery provided in the embodiment of the present application is a negative electrode-free lithium battery. Applying the above-mentioned composite positive electrode material to the negative electrode-free lithium battery is beneficial to effectively improve its safety performance.

[0081] In the negative electrode-free lithium battery, there is no conventional negative electrode active material layer (graphite, silicon) on the negative electrode current collector. The negative electrode current collector can be used to receive lithium ions released from the positive electrode active material, thereby achieving the purpose of energy storage. Therefore, the thickness of the negative electrode current collector not only affects the conduction function of the negative electrode sheet, but also affects the safety of the battery. In this solution, in terms of the safety of the negative electrode-free lithium battery, the appropriate current collector thickness is conducive to balancing the resistance and reducing the heat diffusion when the battery is thermally runaway.

[0082] The embodiment of the present application applies the above composite positive electrode material to a non-negative electrode lithium battery, showing high safety and further improving capacity and cycle performance. At the same time, the simplification of the composite positive electrode material and the non-negative electrode lithium battery process also greatly reduces the production cost. Therefore, the battery has low cost and high capacity, and can be applied to large-scale production.

[0083] A fifth aspect of an embodiment of the present application provides an electrical device comprising the above-mentioned battery.

[0084] In a specific example, the electrical device may be an electric car, an electric motorcycle, an electric bicycle, a mobile phone, a computer, a camera, an e-book player or a wearable device.

[0085] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0086] Example 1

[0087] This embodiment provides a composite positive electrode material, the raw materials are: 90wt% lithium iron manganese phosphate (LFMP) and 10wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0088] Example 2

[0089] This embodiment provides a composite positive electrode material, the raw materials are: 80wt% lithium iron manganese phosphate (LFMP) and 20wt% ternary material NCM712 (LiNi 0.7 Co0.1 Mn 0.2 O2).

[0090] Example 3

[0091] This embodiment provides a composite positive electrode material, the raw materials are: 70wt% lithium iron manganese phosphate (LFMP) and 30wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0092] Example 4

[0093] This embodiment provides a composite positive electrode material, the raw materials are: 60wt% lithium iron manganese phosphate (LFMP) and 40wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0094] Example 5

[0095] This embodiment provides a composite positive electrode material, the raw materials are: 50wt% lithium iron manganese phosphate (LFMP) and 50wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0096] Example 6

[0097] This embodiment provides a composite positive electrode material, the raw materials are: 50wt% lithium iron phosphate (LFP) and 50wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0098] Example 7

[0099] This embodiment provides a composite positive electrode material, the raw materials are: 50wt% lithium iron manganese phosphate (LFMP) and 50wt% binary material NM55 (LiNi 0.5 Mn 0.5 O2).

[0100] In the above-mentioned Examples 1 to 7, the average particle size of the first component is 400 nm, and the average particle size of the second component is 3 μm.

[0101] Comparative Example 1

[0102] This comparative example provides a positive electrode material, the raw materials are: 0wt% lithium iron manganese phosphate (LFMP) and 100wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2), the average particle size of the ternary material is 3μm.

[0103] Comparative Example 2

[0104] This comparative example provides a positive electrode material, the raw materials are: 100wt% lithium iron manganese phosphate (LFMP) and 0wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2), the average particle size of lithium iron manganese phosphate is 400nm.

[0105] Comparative Example 3

[0106] This embodiment provides a composite positive electrode material, the raw materials are: 40wt% lithium iron manganese phosphate (LFMP) and 60wt% ternary material NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2), the average particle size of lithium iron manganese phosphate is 400nm, and the average particle size of the ternary material is 3μm.

[0107] Application Cases

[0108] This embodiment provides a battery, and the specific preparation method is as follows:

[0109] Positive electrode sheet: The binder polytetrafluoroethylene is dispersed in nitrogen methyl pyrrolidone at a mass ratio of 1:16, and stirred at 2000rpm for 2h to obtain a glue with a viscosity of 2500mPa·s. Then, the conductive agent graphene is added to the above glue and stirred at 2000rpm for 2h. Then, the positive electrode materials provided in Examples 1 to 7, Comparative Example 1 and Comparative Example 3 are added and stirred at 2000rpm for 4h. Nitrogen methyl pyrrolidone is added and stirred slowly, and vacuum defoaming is performed after the viscosity of the slurry is adjusted to meet the standard for standby use. The prepared mixed positive electrode slurry is coated on an aluminum foil with a conductive coating. The thickness of the carbon coating layer in the conductive coated aluminum foil is 3μm. After coating, it is rolled, slit, and die-cut into positive electrode sheets for standby use. Among them, the mass of the composite positive electrode material, binder, and conductive agent is 95:2:3.

[0110] Negative electrode current collector: copper foil current collector with a thickness of 8 μm.

[0111] Diaphragm: PE (polyethylene) diaphragm with a thickness of 12μm.

[0112] Battery assembly: The positive electrode sheet, negative electrode current collector and diaphragm are stacked to form a battery cell, the positive and negative electrode tabs are welded and led out, and then the battery cell is placed in an aluminum plastic film. After baking, the electrolyte is injected, and after packaging, formation, capacity division and other processes, a 10Ah soft-pack battery is made.

[0113] The batteries prepared using the composite positive electrode materials of Examples 1 to 7 are named 1#, 2#, 3#, 4#, 5#, 6# and 7#, respectively; the batteries prepared using the positive electrode materials of Comparative Examples 1 and 3 are named D1#, D2# and D3#, respectively.

[0114] Performance Test:

[0115] 1. Test method.

[0116] (1) Capacity test method: The battery obtained above was tested at an ambient temperature of 25±3°C, charged to a full charge state of 4.3V at 0.2C, and then discharged to a voltage of 2.7V at 0.5C; the average discharge capacity of the positive electrode material in the first three times was calculated.

[0117] (2) Safety performance test method: According to the national standard GB38031-2020, the above-obtained battery was tested and charged to 100% SOC for needle puncture, furnace temperature, and overcharge tests.

[0118] (3) Cycling performance test method: charge to 4.3V at 0.2C constant current and constant voltage, then discharge at 0.5C, cycle at 80% DOD (depth of discharge), and record the number of cycles for which the cycle retention rate is 80%.

[0119] 2. Test results.

[0120] The results of capacity test, cycle test and safety performance test are shown in Table 1.

[0121] Table 1 Performance test results

[0122]

[0123] From the analysis in Table 1, we can see that the composite material prepared by mixing lithium manganese iron phosphate into the ternary material and using the composite material in the battery shows no thermal runaway phenomenon in the needle puncture test results, and as the proportion of manganese iron phosphate increases, the battery surface temperature also decreases significantly. In summary, it can be seen that the mixing of lithium manganese iron phosphate effectively prevents the chain reaction of the ternary material during thermal runaway, improves the thermal stability of the overall mixed positive electrode material, and makes the negative electrode-free lithium battery show excellent safety performance.

[0124] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite positive electrode material, characterized in that: comprising a first component and a second component; The first component includes LiFePO4, LiCoPO4, LiMnPO4, LiNiPO4 and LiMn x Fe 1-x At least one of PO4; wherein 0.2≤x≤0.8; The second component includes LiNi y B z C 1-y-z O2; wherein B includes at least one of Co, Al and Mn, C includes at least one of Co, Al and Mn, 0 <y<1,0<z<1; The mass ratio of the first component to the second component is (9-5):(1-5).

2. The composite positive electrode material according to claim 1, characterized in that The mass ratio of the first component to the second component is (7-5):(3-5).

3. The composite positive electrode material according to claim 1 or 2, characterized in that: The LiNi y B z C 1-y-z O2, wherein B is one of Co, Al and Mn, C is one of Co, Al and Mn, and B and C are different.

4. The composite positive electrode material according to any one of claims 1 to 3, characterized in that: The first component is LiMn x Fe 1-x PO4.

5. The composite positive electrode material according to any one of claims 1 to 4, characterized in that: The particle size of the first component is smaller than the particle size of the second component.

6. A positive electrode sheet, characterized in that: The composite positive electrode material comprises the composite positive electrode material according to any one of claims 1 to 5.

7. The positive electrode sheet according to claim 6, characterized in that: It comprises a positive electrode current collector and an active material layer, wherein the active material layer comprises the composite positive electrode material according to any one of claims 1 to 5.

8. The positive electrode sheet according to claim 7, characterized in that: The mass percentage of the composite positive electrode material in the active material layer is 90wt% to 95wt%.

9. A battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 6 to 8.

10. The battery according to claim 9, characterized in that Also included is a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector.

11. The battery according to claim 11 or 12, characterized in that: The negative electrode current collector includes at least one of copper foil, porous copper foil and brass foil.

12. The battery according to any one of claims 9 to 11, characterized in that: The battery is a lithium battery without a negative electrode.

13. An electrical equipment, characterized in that: A battery comprising any one of claims 9 to 12.

Citation Information

Patent Citations

  • Positive active material and preparation method thereof, cathode material of lithium ion battery and preparation method thereof, as well as lithium ion battery

    CN105470495A

  • Nanometer lithium squarate and preparation method thereof, positive plate and lithium battery

    CN115417754A

  • Positive plate and lithium ion battery

    CN116031362A

  • Electrolyte, lithium metal battery, preparation method of lithium metal battery and electric device

    CN116231085A

  • Cathode active material, secondary battery and preparation method

    CN116504961A

Cited By

  • Composite positive electrode material and preparation method therefor, positive electrode sheet, battery, and electric device

    WO2026092244A1